Kinetics of reductive alkylations of phenylenediamines: influence of substrates isomeric structure - Roy, Debdut; Chaudhari, Amit S.; Chaudhari, Raghunath V. (Chemical Engineering Science, 2010)
Reductive alkylation of ortho-, meta- and para-phenylenediamines (PDAs) with methyl ethyl ketone (MEK) has been studied in a semi-batch slurry reactor in the presence of a commercial 3% Pt/Al(2)O(3) catalyst. It was observed that the PDA isomers differ remarkably from each other in their activity in reductive alkylation and product distribution. The activity was found to decrease in the following order: PPDA > OPDA > MPDA. To understand the substrate structure-activity correlation, the homogeneous equilibrium reactions involved in the alkylation step and the overall catalytic reactions were studied separately. Kinetics of reductive alkylation of PDAs with MEK as a solvent and alkylating agent with 3% Pt/Al(2)O(3) catalyst was studied in a semi-batch slurry reactor over a temperature range of 373-453K and pressure range of 2.07-6.21 MPa. Semi-batch slurry reactor models were developed and kinetic parameters were estimated by fitting the integral batch reactor data at different temperatures to understand the influence of different reaction steps on the activity and selectivity of different products. Published by Elsevier Ltd.
20th International Symposium on Chemical Reaction Engineering, Kyoto, JAPAN, SEP, 2008
Keywords: Batch; catalysis; kinetics; Multiphase reactions; Phenylenediamines; Reaction engineering; Reductive alkylation

Kinetics of hydroformylation of 1-octene in ionic liquid-organic biphasic media using rhodium sulfoxantphos catalyst - Deshpande, R. M.; Kelkar, Ashutosh A.; Sharma, A.; Julcour-Lebigue, C.; Delmas, Henri (Chemical Engineering Science, 2011)
Biphasic hydroformylation of 1-octene was performed using rhodium sulfoxantphos catalyst dissolved in [BuPy][BF(4)] ionic liquid. Preliminary experiments proved this system to retain the catalytic complex within the ionic liquid phase and to maintain a high selectivity towards the linear aldehyde (n:iso ratio of 30) over several cycles. Process parameter investigation showed a first order dependence of the initial rate with respect to the catalyst and 1-octene concentrations, but a more complex behavior with respect to hydrogen (fractional order) and carbon monoxide partial pressures (inhibition at high pressures). Different mathematical models were selected based on the trends observed and evaluated for data fitting. Also, rate models were derived from a proposed mechanism, using Christiansen matrix approach. To calculate concentrations of substrates in the catalytic phase as required by this kinetic modeling, solubility measurements were preformed for the gases (pressure drop technique), as well as for 1-octene and n-nonanal (thermogravimetry analysis). (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Biphasic catalysis; Butylpyridinium tetrafluoroborate; kinetics; Parameter identification; Reaction engineering; solubility